TRAFFIC CONGESTION DETECTION USING WIRELESS SENSOR NETWORK - Jalil, Muhammad Azizulhariz (Universiti Teknologi Petronas, 2013)
Nowadays, traffic congestion has becoming one of the biggest problems faced by developing and developed countries. The project aims to produce a solution for traffic congestions using a wireless sensor network by effectively conveying real time information to the public. The wireless sensor network consists of sensors that deployed in each vehicle and have the ability to communicate with each other via wireless motes. An algorithm decides the occurrence of the traffic congestion from data obtained by the speed and distance sensors. At the end of the project, a simple prototype is built using a distance sensor and a motor connected to a speed sensor to represent the sensor connected to the wheels of a vehicle.